A highly efficient layered double hydroxide catalyst for direct ethoxylation of butyl acetate to oligo‐ethylene glycol butyl ether acetates. (13th April 2016) - Zhang, Jinchang; Shi, Lei; Meng, Yan; Fu, Yang; Liu, Zhaobin; Zhu, Jianmin
Abstract : A novel synthetic route that directly insertsethylene oxide into butyl acetate without any labile hydrogen to produce oligo‐ethylene glycol butyl ether acetates is developed using an efficient acid–base bifunctional catalyst. The layered double hydroxide materials, which have structures similar to that of hydrotalcite, are synthesized using co‐precipitation methods. After modification by organic acid, the as‐prepared catalysts exhibit higher butyl acetate conversion andethylene oxide catalytic activity with narrow ethylene glycol butyl ether acetate adduct distribution. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A novel synthetic route that directly inserts ethylene oxide (EO) into butyl acetate (BAC) without any labile hydrogen to produce oligo‐ethylene glycol butyl ether acetates (oligo‐EBACs) is developed using an efficient acid–base bifunctional catalyst. After modification by organic acid, the as‐prepared catalysts exhibit higher BAC conversion and EO catalytic activity with narrow EBAC adduct distribution. The molar ratio of BAC to EO is an important variable, significantly affecting the conversion and selectivity.